Effects of Sample and Indenter Configurations of Nanoindentation Experiment on the Mechanical Behavior and Properties of Ductile Materials - Koloor, Seyed Saeid Rahimian; Karimzadeh, Atefeh; Tamin, Mohd Nasir; Abd Shukor, Mohd Hamdi (MDPI, 2018)
The nanoindentation test is frequently used as an alternate method to obtain the mechanical properties of ductile materials. However, due to the lack of information about the effects of the sample and indenter physical configurations, the accuracy of the extracted material properties in nanoindentation tests requires further evaluation that has been considered in this study. In this respect, a demonstrator ductile material, aluminum 1100, was tested using the Triboscope nanoindenter system with the Berkovich indenter. A 3D finite element simulation of the nanoindentation test was developed and validated through exact prediction of the structural response with measured data. The validated model was then employed to examine the effects of various test configurations on the load-displacement response of the sample material. These parameters were the different indenter edge-tip radii, different indentation depths, different sample tilts, and different friction conditions between the indenter and the material surface. Within the range of the indenter edge-tip radii examined, the average elastic modulus and hardness were 78.34 ± 14.58 and 1.6 ± 0.24 GPa, respectively. The different indentation depths resulted in average values for the elastic modulus and hardness of 77.03 ± 6.54 and 1.58 ± 0.17 GPa, respectively. The uneven surface morphology, as described by the inclination of the local indentation plane, indicated an exponential increase in the extracted values of elastic modulus and hardness, ranging from 71.83 and 1.47 GPa (for the reference case, θ = 0°) to 243.39 and 5.05 GPa at θ = 12°. The mechanical properties that were obtained through nanoindentation on the surface with 6° tilt or higher were outside the range for aluminum properties. The effect of friction on the resulting mechanical response and the properties of the material was negligible.